It can't be all of them!

Geometry Level 4

M = k = 1 n 1 cos ( 2 π n k ) \large M= \large \sum_{k=1}^{n-1} \cos\left( \frac{2\pi}n k \right)

Above shows a trigonometric identity. What is the value of M M ?

There is insufficient information 1 1 1 -1 2 2 0 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let e 2 π i n e^{\frac {2 \cdot \pi \cdot i}{n}} be one primitive root of x n 1 x^n - 1 = 0 = ( x - 1)( x n 1 + x n 2 + . . . + x + 1 x^{n-1} + x^{n-2} + ... + x + 1 ). Then e 2 ( n 1 ) π i n + e 2 ( n 2 ) π i n + . . . + e 2 π i n + 1 = 0 e^{\frac {2 \cdot {(n-1)} \cdot \pi \cdot i}{n}} + e^{\frac {2 \cdot {(n-2)} \cdot \pi \cdot i}{n}} + ... + e^{\frac {2 \cdot \pi \cdot i}{n}} + 1 = 0 . Now only have to review the real part of this last identity and it gives the solution. (n > 1)

Can you please explain the last sentence of your solution?

Atharva Bagul - 5 years, 7 months ago

Log in to reply

Yes, e i x = c o s ( x ) + i s i n ( x ) e^{ix} = cos (x) + i sin (x) and for Moivre's Theorem, ( c o s ( x ) + i s i n ( x ) ) n (cos (x) + i sin(x))^{n} = ( e i x ) n (e^{ix})^{n} = e i n x e^{inx} = cos (nx) + i sin(nx) . Therefore, e 2 ( n 1 ) π i n + e 2 ( n 2 ) π i n + . . . + e 2 π i n + 1 = 0 e^{\frac {2 \cdot {(n-1)} \cdot \pi \cdot i}{n}} + e^{\frac {2 \cdot {(n-2)} \cdot \pi \cdot i}{n}} + ... + e^{\frac {2 \cdot \pi \cdot i}{n}} + 1 = 0 \Rightarrow cos 2 ( n 1 ) π n \frac {2 \cdot {(n-1)} \cdot \pi}{n} + i sin 2 ( n 1 ) π n \frac {2 \cdot {(n-1)} \cdot \pi}{n} + cos 2 ( n 2 ) π n \frac {2 \cdot {(n-2)} \cdot \pi}{n} + i sin 2 ( n 2 ) π n \frac {2 \cdot {(n-2)} \cdot \pi}{n} + ... + cos 2 π n \frac {2 \cdot \pi}{n} + i sin 2 π n \frac {2 \cdot \pi}{n} + 1 = 0. Now, take the real part of this identity and it will give you the result. You also can take the imaginary part and it gives another beautiful result. e 2 ( n 1 ) π i n + e 2 ( n 2 ) π i n + . . . + e 2 π i n + 1 = 0 e^{\frac {2 \cdot {(n-1)} \cdot \pi \cdot i}{n}} + e^{\frac {2 \cdot {(n-2)} \cdot \pi \cdot i}{n}} + ... + e^{\frac {2 \cdot \pi \cdot i}{n}} + 1 = 0 because ( e 2 i π n 1 e^{\frac {2 \cdot i \cdot \pi}{n}} - 1 ) \neq 0 (n > 1)

Guillermo Templado - 5 years, 7 months ago
Rishi Sharma
Nov 12, 2015

J E E s t y l e : s i n c e t h i s i s a n i d e n t i t y i n n l e t n = 2 M = c o s ( 2 π 2 ( 2 1 ) ) M = c o s ( π ) = 1 P S : i t i s n o t t h e r i g h t w a y y o u s h o u l d u s e g u i l l e r m o s w a y . JEE\quad style:-\\ since\quad this\quad is\quad an\quad identity\quad in\quad n\quad let\quad n=2\\ M=cos(\frac { 2\pi }{ 2 } (2-1))\\ M=cos(\pi )=-1\\ PS:-\quad it\quad is\quad not\quad the\quad right\quad way\quad you\quad should\quad use\\ guillermo's\quad way.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...